Desulfurization–Oxygenation of Chiral 1,3-Thiazolidine-2-thiones and 1,3-Oxazolidine-2-thiones Using Propylene Oxide and Microwave Irradiation - Minor-Villar, Leticia; Tello-Aburto, Rodolfo; Olivo, Horacio F.; Fuentes, Aydee; Romero-Ortega, Moises (Synlett, 2012)
An efficient method for the desulfurization–oxygenation of 1,3-thiazolidine-2-thiones and 1,3-oxazolidine-2-thiones using propylene oxide and employing microwave irradiation is described. This strategy of oxygenation of the thiocarbonyl group provides an attractive methodology to prepare chiral 1,3-thiazolidin-2-ones and 1,3-oxazolidin-2-ones from the corresponding precursors in good yields.
Keywords: thiazolidinethiones; oxazolidinethiones; thiazolidinones; propylene oxide; chiral auxiliaries.